Optic nerve metastasis from a mediastinal carcinoid tumour. Issue 8 (August 1976) - Fishman, M. L.; Rosenthal, S.
Abstract : A 25-year-old man with a rapidly progressive metastatic carcinoid tumour arising in the mediastinum developed a metastasis to the optic nerve. This is the first instance in the literature of an ocular metastasis from this variant of carcinoid tumour. The ocular pathology, ultrastructure, and recent information on the derivation of this tumour, believed to originate in the thymus, are presented.